Enfermedad hipertensiva del embarazo: Valor predictivo del Roll Over Test en el hospital regional de Loreto – Punchana período Diciembre 1994 - Julio 1995 - Cabrera Tuesta, Llimy Andrex (1996)
In this work experimental research prospective it is detected in the early stage, hypertensive disease of pregnancy by a simple test called roll over test conducted at the regional hospital of Loreto in the period from December 1994 to July 1995. It was noted that a total of 1,485 births, 229 - accidents ernbarazo had hypertensive disease (15.42%) of which 165 patients had preeclampsia (11.11%), 23 eclampsia (1.55%) and 41 patients 2.76% transient hypertension. For the roll over test, the total of pregnant women in the study was 114, with 56 nulliparous, primiparous and 32 multiparous 26 between the 28-32 weeks gestation who attended prenatal care. A pregnant mentioned we applied the roll over test, the results were kept in reserve until postpartum. Our purpose was to determine the predictive value of Over Test and demonstrate its utility in the early detection of the disease Hypertensive Pregnancy. The positive predictive value of the test in total, pregnant women was 81. 25%, with a x2 of 36.70 and with a statistical significance of O, in nulliparous was 16.71% with 36.70 X2 and statistical significance, Or in primiparous and multiparous was 77.78% with 21.66 X2 and statistical significance of 0.0000033. Differences resulting pressures in the test had no more significant value in the development of the different entities of the hypertensive disease of pregnancy.